2023
DOI: 10.3390/jfb14060318
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized Porcine Conjunctiva in Treating Severe Symblepharon

Abstract: This prospective study aimed to evaluate the effectiveness of decellularized porcine conjunctiva (DPC) in the management of severe symblepharon. Sixteen patients with severe symblepharon were enrolled in this study. After symblepharon lysis and Mitomycin C (MMC) application, tarsus defects were covered with residual autologous conjunctiva (AC), autologous oral mucosa (AOM), or DPC throughout the fornix, and DPC was used for all the exposed sclera. The outcomes were classified as complete success, partial succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Their investigation showed that DPC used alongside AC or AOM resulted in complete treatment success in 75% of cases, partial success in 18.75% and failure in 6.25%. Thus, they concluded that DPC is a viable option to treat severe symblepharon, resulting in significant recovery in eye mobility and fornix depth especially when combined with autologous mucosa [69]. Chen's group created enhanced decellularized porcine pericardium scaffolds for conjunctival reconstruction by crosslinking them with aspartic acid and human endothelial growth factor.…”
Section: Decellularized Graftsmentioning
confidence: 99%
“…Their investigation showed that DPC used alongside AC or AOM resulted in complete treatment success in 75% of cases, partial success in 18.75% and failure in 6.25%. Thus, they concluded that DPC is a viable option to treat severe symblepharon, resulting in significant recovery in eye mobility and fornix depth especially when combined with autologous mucosa [69]. Chen's group created enhanced decellularized porcine pericardium scaffolds for conjunctival reconstruction by crosslinking them with aspartic acid and human endothelial growth factor.…”
Section: Decellularized Graftsmentioning
confidence: 99%